Understanding Market Evolution of CAD Systems, 1970s to 2000s - Holtz, W. Bradley (IEEE annals of the history of computing, 2025)
From its inception in the 1970s through the early twentieth century, internal market forces and external factors shaped both individual computer-aided design (CAD) vendors and the commercial CAD industry as a whole. This article supplies perspective and context for this evolution to provide a better understanding of the early stages of commercialization of other technologies. The goal of this article is to provide context with which to view and understand the first 30 years of development of the CAD industry, which is necessary to understand both the global and industry-specific factors that shaped the products and their markets. This is achieved by detailing the market dynamics that influenced how and why companies succeeded and failed in the CAD industry, revealing how factors such as globalization and the offshoring of labor affected the types of people working in the industry, which in turn affected the features and functionality of available products.